Idenfikasi Kesalahan Siswa Dalam Menyelesaikan Soal Bilangan Berpangkat dan Bentuk Akar : Idenfikasi Kesalahan Siswa Dalam Menyelesaikan Soal Bilangan Berpangkat dan Bentuk Akar Di kelas IX SMPN 2 Tasik Payawan - Febri Liansa Putri; Sarjoko Yohanes; Muhamad Hamdani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
The background of this research is that there are still many class IX students of SMPN 2 Tasik Payawan who make mistakes in solving problems of numbers with exponents and roots. The purpose of this study was to describe the errors and causal factors made by class IX students of SMPN 2 Tasik Payawan in solving problems of numbers with exponents and roots. This research is descriptive-qualitative. The implementation of this research is in the odd semester of the 2021/2022 academic year. The subjects of this study were 20 students of class XI SMA Negeri 1 Tewah 2021/2022, then 3 students were selected to be interviewed. Data collection techniques using tests and interviews. The process of taking test results and interviews is carried out by taking into account the health protocol, namely offline/face-to-face. The research instruments were test sheets and interview guidelines. The test in this study was in the form of 4 questions of numbers with exponents and a root form in the form of a description which had previously been studied by three raters consisting of two lecturers of the Mathematics Education Study Program at the University of Palangka Raya and one Mathematics teacher at SMPN 2 Tasik Payawan with the result that all items questions can be used. Analysis of the data used by means of reduction, presentation, and drawing conclusions. Based on the results of data analysis, the errors made by students in solving problems of numbers with exponents and roots include: 1) Adding and subtracting questions whose results are the questions themselves. 2) Solve problems that are not in accordance with the nature of the root form. 3) Wrong in performing arithmetic operations. Factors causing students to make mistakes in solving problems of numbers with exponents and root forms in accordance with the cognitive domain, namely knowledge is the lack of students about the symbols of root forms and lack of understanding of students about the concept of root forms, understanding is the lack of students' ability to understand the properties of root forms related to principles and operations in solving root forms, application is the lack of students' ability to apply the properties of root forms.